Divine Constitution Perspective On the Reactualization of Allah’s Law - Arlis, Arlis; Zulfan, Zulfan; Azwar, Zainal; Taufiq, Arif (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The main question of this study is how divine constitution perspective on the reactualization of Allah's law. The background of the problem is the inequality between the law at the ideal and factual levels. Ideally, the degree of law is within the corridors and the degree of Allah's law, but the facts show that the nuances of the law are more oriented towards the product of man alone. The research position is very interesting with the variety of legal concepts. Questions are discussed with normative legal studies with qualitatively analyzed. The main result is the position of Allah’s law is the single best law and has the highest degree for a sure person. Allah’s law is a system of laws that contains the maslahat of the world and the hereafter. Allah’s law is fixed and some is changing whose content material is comprehensive and accordance with the needs of the times, places, circumstances, intentions and traditions. Allah commissioned the apostles, bringing down the books and the suhuf-suhuf as the basic benchmark and the main reference of the law. The last treatise was received by the Muhammad SAW with the guidance of the Qur'an and the sunnah.. Allah's law must be obeyed, and the disobedient are obeyed. Taqwa is the noblest level in the application of the law of Allah. Allah guarantees a successful life and goes to heaven for people who obey Allah's laws.